A Weak Limit Theorem for Galton-Watson Processes in Varying Environments - Zhenlong Gao; Yanhua Zhang (Journal of Applied Mathematics)
We extend Donsker’s theorem and the central limit theorem of classical Galton-Watson process to the Galton-Watson processes in varying environment.